Can Reducing Faults Prevent Vulnerabilities? - Kuhn, Rick; Raunak, Mohammad; Kacker, Raghu (Computer (00189162), 2018)
Most security vulnerabilities result from ordinary coding errors. What does this mean for the prospects of more secure software?